A new method of bottleneck analysis for manufacturing systems. (January 2019) - Tang, He
Abstract: One of the measurements of manufacturing systems is Overall Equipment Effectiveness (OEE). This paper reviews OEE, discusses the throughput losses from the three factors of OEE, and explores the hidden information in OEE. This paper proposes a new method based on OEE to identify the bottlenecks of complex manufacturing systems. The new method considers not only the output of a manufacturing system but also the influences from its upstream and downstream systems. Therefore, the new method can reveal the true fulfillment and competence of a manufacturing system, which can guide improvement efforts.